Short- and long-term effects of altered point of ground reaction force application on human running energetics - Ekizos, A.; Santuz, A.; Arampatzis, A. (The Journal of Experimental Biology, 2018)
The current study investigates the effect of altering the point of force application (PFA) from the rearfoot towards the fore of the foot on the metabolic energy consumption and the influence of transitioning to this technique over a short or a longer timeframe. The participants were randomly assigned into two experimental and one control group: a short-term intervention group (STI, N=17; two training sessions), a long-term intervention group (LTI, N=10; 14-week gradual transition) and a control group (CG, N=11). Data were collected at two running velocities (2.5 and 3.0 m s-1). The cost coefficient (i.e. energy required per unit of vertical ground reaction force; J N-1) decreased (P<0.001) after both interventions due to a more anterior PFA during running (STI: 12%, LTI: 11%), but led to a higher (P<0.001) rate of force generation (STI: 17%, LTI: 15.2%). Dynamic stability of running showed a significant (P<0.001) decrease in the STI (2.1%), but no differences (P=0.673) in the LTI. The rate of metabolic energy consumption increased in the STI (P=0.038), but remained unchanged in the LTI (P=0.660). The CG had no changes. These results demonstrate that the cost coefficient was successfully decreased following an alteration in the running technique towards a more anterior PFA. However, the energy consumption remained unchanged because of a simultaneous increase in rate of force generation due to a decreased contact time per step. The increased instability found during the short-term intervention and its neutralization after the long-term intervention indicates a role of motor control errors in the economy of running after acute alterations in habitual running execution.